Cannery Row - Steinbeck, John, 1902-1968. (London : Penguin Books, 2012)
Recounts the adventures and misadventures of cannery workers living in the run-down waterfront section of Monterey, California.
Adult.
Adult
Keywords: Community life -- Fiction; Marine biologists -- Fiction; Community life -- Fiction; Love stories; Marine biologists -- Fiction; Cannery Row (Monterey, Calif.) -- Fiction; Monterey (Calif.) -- Fiction; Cannery Row (Monterey, Calif.) -- Fiction; Monterey (Calif.) -- Fiction; Love stories